2022
DOI: 10.1038/s41380-022-01561-3
|View full text |Cite
|
Sign up to set email alerts
|

Translocator protein (18kDa) TSPO: a new diagnostic or therapeutic target for stress-related disorders?

Abstract: Efficient treatment of stress-related disorders, such as depression, is still a major challenge. The onset of antidepressant drug action is generally quite slow, while the anxiolytic action of benzodiazepines is considerably faster. However, their long-term use is impaired by tolerance development, abuse liability and cognitive impairment. Benzodiazepines act as positive allosteric modulators of ɣ-aminobutyric acid type A (GABA A ) receptors. 3α-reduced neurosteroids such as allopregnanolone also are positive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 122 publications
0
24
1
Order By: Relevance
“…It is expressed to varying degrees in multiple tissues, with the highest levels of expression found in steroidogenic tissues and relatively low expression in the central nervous system. In the brain, TSPO can be detected predominantly in microglia and reactive astrocytes [ 9 ], where its expression is upregulated in the context of inflammation, neurodegeneration, and malignant neoplasia [ 10 , 11 ]. Although the role of TSPO in de novo steroidogenesis was questioned in view of various genetic TSPO deletion models [ 12 , 13 , 14 , 15 ], our recent studies support a role of TSPO expression as well as of TSPO ligands in the regulation of pregnenolone synthesis in mouse BV-2 and human C20 microglia cells [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed to varying degrees in multiple tissues, with the highest levels of expression found in steroidogenic tissues and relatively low expression in the central nervous system. In the brain, TSPO can be detected predominantly in microglia and reactive astrocytes [ 9 ], where its expression is upregulated in the context of inflammation, neurodegeneration, and malignant neoplasia [ 10 , 11 ]. Although the role of TSPO in de novo steroidogenesis was questioned in view of various genetic TSPO deletion models [ 12 , 13 , 14 , 15 ], our recent studies support a role of TSPO expression as well as of TSPO ligands in the regulation of pregnenolone synthesis in mouse BV-2 and human C20 microglia cells [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was already shown that spatial volumes of TSPO-PET add complementary information to amino acid PET since the spatial agreement of both imaging targets was rather poor ( 3 ). Ultimately, TSPO agonists or antagonists could also act as direct modulators of TSPO expression in gliomas ( 4 ) and such therapies would profit from monitoring of altered target expression by TSPO-PET. The value of TSPO imaging in glioma was already determined in prognostication and detection of tumor heterogeneity ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…TSPO may not only serve as a diagnostic marker in combination with other neuroimaging modalities, but it might also exert as a direct target for putative therapeutic effects in stress-related diseases such as MDD ( Rupprecht et al, 2022 ). While the present results may present microglia as a therapeutic target, a treatment trial with minocycline failed to rectify the elevated TSPO-PET binding in a cohort of patients with treatment-resistant depression ( Attwells et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%